Fatty acid composition of mature breast milk in Brazilian women - Silva, Maurício H.L.; Silva, Marco Túlio C.; Brandão, Sebastião C.C.; Gomes, José C.; Peternelli, Luiz A.; Franceschini, Sylvia do C.C. (Food Chemistry, 2005)
This work analyzed the fatty acid composition of mature milk samples, weekly obtained from eight Brazilian women between the 4th and 13th lactation weeks. A questionnaire was weekly applied to observe their eating habits. Saturated fatty acids constituted 39.7% of the total fatty acids. De novo fatty acids and long chain saturated fatty acids presented levels of 15.9% and 23.8%, respectively. trans-Fatty acid content was very low (2.36%). Unsaturated fatty acids constituted 50.9% of the total fatty acids, with over half being monounsaturated fatty acids (27.6%). Polyunsaturated fatty acids showed levels of 23.3%, with high linoleic and α-linolenic acid contents (20.3% and 1.43%, respectively). Arachidonic acid had a content of 0.53%, while docosahexaenoic acid content was 0.14%, values considered adequate for the needs of breast-fed infants.
Keywords: Human milk; Fatty acid composition; Brazilian women